2022
DOI: 10.1186/s12909-022-03454-z
|View full text |Cite
|
Sign up to set email alerts
|

Medical school curriculum in the digital age: perspectives of clinical educators and teachers

Abstract: Background There is a need to reexamine Singapore’s medical school curricula in light of the increasing digitalization of healthcare. Notwithstanding Singapore’s digital competitiveness, there is a perceived gap in preparing its medical students for the digital age. Furthermore, limited research has evaluated the extent to which skills in using digital technologies should be taught to medical students in Asian medical schools to prepare them for future clinical practice- a gap that is filled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Yet, while some medical schools in countries such as Germany and Switzerland have made training in telemedicine, digital medicine and data science mandatory for its students [ 22 , 36 ], these courses are largely taught as electives or only briefly within Singapore’s formal medical school curricula. Additionally, while a memorization-based and risk-averse curricula form a common challenge of most medical schools in developed economies [ 12 , 39 , 40 ], what forms a significant barrier to innovation and curricular implementation of digital topics in Singapore is its hectic clinical environment, which offers very limited time for its trainees to explore digital technologies and embark on innovation projects of interest. A study reported that the professional burnout rate among junior doctors in Singapore was higher than that in the USA despite both countries sharing similar residency programs and Accreditation Council for Graduate Medical Education (ACGME) guidelines [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, while some medical schools in countries such as Germany and Switzerland have made training in telemedicine, digital medicine and data science mandatory for its students [ 22 , 36 ], these courses are largely taught as electives or only briefly within Singapore’s formal medical school curricula. Additionally, while a memorization-based and risk-averse curricula form a common challenge of most medical schools in developed economies [ 12 , 39 , 40 ], what forms a significant barrier to innovation and curricular implementation of digital topics in Singapore is its hectic clinical environment, which offers very limited time for its trainees to explore digital technologies and embark on innovation projects of interest. A study reported that the professional burnout rate among junior doctors in Singapore was higher than that in the USA despite both countries sharing similar residency programs and Accreditation Council for Graduate Medical Education (ACGME) guidelines [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been initiatives to introduce courses related to digital technologies in the core curriculum, such as informatics and digital health, they vary in content and duration across the three medical schools in Singapore. Current training in the application of these skills to clinical practice is also limited [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zainal H., Xin X., Thumboo J., Fong K.Y. point out the two advantages of using digital technology in training, based on interviews with experts in the field of methodological support of medical education -promoting a culture of innovation and performance improvement [2]. At the same time, their conclusions regarding the negative effects of digital technologies are relevant and applicable not only to medical, but also to teachers' education.…”
Section: Introductionmentioning
confidence: 98%
“…The researchers come to the conclusion that when developing tasks for the lessons within this method, it is necessary to focus on the features of students' perception. Referring to Korthagen's "The Onion" model (environment, behavior, competencies, beliefs, identity, and mission), the authors emphasize that in order to function properly in PBL, teachers' teaching perspectives, as measured by those six aspects, should be in a student-centered direction [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence-based research has shown that digital learning promotes SDL and that it is convenient for professionals to access courses through digital devices in clinical settings, positively impacting learners’ achievements [ 20 , 21 ]. When digital media are designed to be emerging and habit-forming in the digital age, it is ideal for educators to use these technologies to enrich, extend, and advance learning in different environments [ 22 , 23 ]. As a result, if educators could build a digital CE programme from the learner’s perspective, making the CE activity more intuitive, readable and enjoyable, they could effectively motivate professionals’ independent learning in various complex work environments.…”
Section: Introductionmentioning
confidence: 99%